Illusory conjunctions in visual short‐term memory: Individual differences in corpus callosum connectivity and splitting attention between the two hemifields. (8th August 2016) - Qin, Shuo; Ray, Nicholas R.; Ramakrishnan, Nithya; Nashiro, Kaoru; O'Connell, Margaret A.; Basak, Chandramallika
Abstract: Overloading the capacity of visual attention can result in mistakenly combining the various features of an object, that is, illusory conjunctions. We hypothesize that if the two hemispheres separately process visual information by splitting attention, connectivity of corpus callosum—a brain structure integrating the two hemispheres—would predict the degree of illusory conjunctions. In the current study, we assessed two types of illusory conjunctions using a memory‐scanning paradigm; the features were either presented across the two opposite hemifields or within the same hemifield. Four objects, each with two visual features, were briefly presented together followed by a probe‐recognition and a confidence rating for the recognition accuracy. MRI scans were also obtained. Results indicated that successful recollection during probe recognition was better for across hemifields conjunctions compared to within hemifield conjunctions, lending support to the bilateral advantage of the two hemispheres in visual short‐term memory. Age‐related differences regarding the underlying mechanisms of the bilateral advantage indicated greater reliance on recollection‐based processing in young and on familiarity‐based processing in old. Moreover, the integrity of the posterior corpus callosum was more predictive of opposite hemifield illusory conjunctions compared to within hemifield illusory conjunctions, even after controlling for age. That is, individuals with lesser posterior corpus callosum connectivity had better recognition for objects when their features were recombined from the opposite hemifields than from the same hemifield. This study is the first to investigate the role of the corpus callosum in splitting attention between versus within hemifields.